2016
DOI: 10.1111/hsc.12339
|View full text |Cite
|
Sign up to set email alerts
|

Informal care for people with chronic psychotic symptoms: four case studies in a San community in South Africa

Abstract: Despite the internationally recognised importance of informal care, especially in settings with limited services, few studies focus on the informal care for people with mental health problems in low- and middle-income countries. Making informal care visible is important for understanding the challenges and identifying the needs to be addressed. This ethnographic case study explored the dynamics of informal care for people with chronic psychotic symptoms in a group of San living in poor socioeconomic circumstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…(), de Wet et al. () and den Hertog & Gilmoor () found that traditional and faith healers were often sought in the first instance. Similarly, studies in Uganda (Abbo et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(), de Wet et al. () and den Hertog & Gilmoor () found that traditional and faith healers were often sought in the first instance. Similarly, studies in Uganda (Abbo et al.…”
Section: Resultsmentioning
confidence: 99%
“…() that explored the effectiveness of a community‐based rehabilitation intervention found that educating the community about mental illness reduced stigma. In examining the way informal care was structured for people with schizophrenia in South Africa, den Hertog & Gilmoor () found that the nuclear family retained the main responsibilities of caring for a relative living with schizophrenia. Although caring responsibilities were shared among the relatives, poverty limited the amount of care provided, often forcing patients to resort to begging to supplement the family's income.…”
Section: Resultsmentioning
confidence: 99%
“… 7 Poverty is a structural problem as 97% of the Khwe and !Xun live on less than one dollar/day and have an unemployment rate of 95%. 19 All learners were from either the !Xun or the Khwe San community. Each community practices a different home language, but all teaching is done in Afrikaans.…”
Section: Methodsmentioning
confidence: 99%
“… 16 , 17 Risk factors for STIs such as unemployment, alcoholism, domestic violence and HIV reported previously on marginalized communities in South Africa 18 were also entrenched among the Khwe and !Xun in Platfontein. 19 , 20 The San Baseline study conducted by the AIDS Foundation of South Africa revealed that 73% of the Platfontein San respondents were not using condoms, had multiple sex partners, and they had low knowledge of HIV and AIDS. 17…”
Section: Introductionmentioning
confidence: 99%
“…Finally, drawing on this investigative process of the proposed study, a hypothesis was developed on how poverty and social and economic processes apply to traditional healers and, specifically, how it can affect traditional healing. Research conducted on healing strategies in southern Africa explain how financial constraints limit access to traditional healing, as there are costs associated with visiting traditional healers (Den Hertog & Gilmoor, 2017). Identifying this gap assisted the researchers to formulate the broad objective of this research: To investigate how social and economic capital affect the process of healing by traditional healers.…”
Section: Setting the Scenementioning
confidence: 99%